2020
DOI: 10.1111/infa.12380
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ abilities to respond to cues for joint attention vary by family socioeconomic status

Abstract: The influence of socioeconomic variability on language and cognitive development is present from toddlerhood to adolescence and calls for investigating its earliest manifestation. Response to joint attention (RJA) abilities constitute a foundational developmental milestone that are associated with future language, cognitive, and social skills. How aspects of the family home environment shape RJA skills is relatively unknown. We investigated associations between family socioeconomic status (SES) —both parent ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 65 publications
(81 reference statements)
3
12
0
Order By: Relevance
“…In light of these findings, the present study included both chronological age and gestation duration in its models, rather than comparing infants matched on age corrected for degree of prematurity. Unsurprisingly, we found that infants become more sophisticated at reading RJA cues from adults as they age, similar to past work (Reilly et al., 2021; Stallworthy et al., 2021). In alignment with past findings of prematurity‐related deficits in early joint attention, findings from this study suggest that chronological and gestational age each positively predicts unique variation in early RJA.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In light of these findings, the present study included both chronological age and gestation duration in its models, rather than comparing infants matched on age corrected for degree of prematurity. Unsurprisingly, we found that infants become more sophisticated at reading RJA cues from adults as they age, similar to past work (Reilly et al., 2021; Stallworthy et al., 2021). In alignment with past findings of prematurity‐related deficits in early joint attention, findings from this study suggest that chronological and gestational age each positively predicts unique variation in early RJA.…”
Section: Discussionsupporting
confidence: 90%
“…In alignment with past findings of prematurity‐related deficits in early joint attention, findings from this study suggest that chronological and gestational age each positively predicts unique variation in early RJA. We also found negative associations between RJA variation and both chronological age and gestation duration, suggesting that infants become more consistent in their responding with age (similar to past work; Reilly et al., 2021; Stallworthy et al., 2021). Unlike past studies that typically collapse potentially meaningful variation in gestational age into the categories of ‘‘preterm’’ versus ‘‘full term,’’ the present study modeled a wide range of gestation durations continuously.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Conditioning DJAA mean scores on age. As presented in Supplementary Information, and consistent with previous reports (Elison et al, 2013;Reilly et al, 2021;Stallworthy, Lasch, et al, 2022), age was significantly correlated with DJAA mean score, r(422) = .57, p < .001. To assess associations between the developmental sophistication of RJA performance and later developmental abilities more precisely, we conditioned DJAA scores on participants' age at the time of DJAA assessment.…”
Section: Analytic Strategysupporting
confidence: 90%